2020
DOI: 10.1002/pssr.202000093
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic Bismuth–Dielectric Structure for Terahertz Photonics

Abstract: Hyperbolic medium is a special class of strongly anisotropic materials described by diagonal permittivity tensor with the principal components being of the opposite signs, which results in a hyperbolic shape of isofrequency contours. These media support propagating electromagnetic waves with extremely large wave vectors exhibiting unique optical properties and applications such as negative refraction, subwavelength imaging, radiative heat transfer manipulation, enhancing spontaneous emission rate (Purcell fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
1
1
0
1
Order By: Relevance
“…The study [14] showed, that the charge carrier plasma frequency, which determines the upper frequency limit of the possibility of detecting radiation, in bulk bismuth lies within the range from 93 to 99 THz (depending on the radiation polarization) at the temperature of 300 K. In case of cooling to the temperature of 80 K the plasma frequency decreases to the values of 59−62 THz, that is in good agreement with the results of the study [15], in which the features of the reflection spectra of doped bismuth−antimony crystals were studied in the long-wave infrared spectrum. However, as shown in the study [16], with a decrease in the bismuth film thickness up to the values of 40 to 150 nm at a temperature of 300 K a decrease in the plasma frequency (compared to bulk samples) up to 55 THz at a thickness of 40 nm and up to 67 THz at a thickness of 150 nm is also observed. Consequently, under the effect of monochromatic radiation of 0.14 THz in Bi 88 Sb 12 at 300 K the radiation absorption will be observed, and to describe the processes the theory of internal photoeffect for semiconductors may be used.…”
Section: Expected Effects and Phenomenasupporting
confidence: 64%
“…The study [14] showed, that the charge carrier plasma frequency, which determines the upper frequency limit of the possibility of detecting radiation, in bulk bismuth lies within the range from 93 to 99 THz (depending on the radiation polarization) at the temperature of 300 K. In case of cooling to the temperature of 80 K the plasma frequency decreases to the values of 59−62 THz, that is in good agreement with the results of the study [15], in which the features of the reflection spectra of doped bismuth−antimony crystals were studied in the long-wave infrared spectrum. However, as shown in the study [16], with a decrease in the bismuth film thickness up to the values of 40 to 150 nm at a temperature of 300 K a decrease in the plasma frequency (compared to bulk samples) up to 55 THz at a thickness of 40 nm and up to 67 THz at a thickness of 150 nm is also observed. Consequently, under the effect of monochromatic radiation of 0.14 THz in Bi 88 Sb 12 at 300 K the radiation absorption will be observed, and to describe the processes the theory of internal photoeffect for semiconductors may be used.…”
Section: Expected Effects and Phenomenasupporting
confidence: 64%
“…The thickness of the bismuth film was chosen toachieve high conductivity and to provide transmission at the same time [37,38]. A thin, almost transparent mica substrate was chosen for THz waves due to its stable geometry and its ability to grow a high-quality bismuth film with a large average crystallit size.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The dispersion of the HMM conforms to a hyperboloid shape [63], with one directional component of permittivity (ε) extending infinitely in the direction where ε is negative. Effective metamaterials with hyperbolic dispersion have been experimentally realized using layered metal-dielectric structures in a repeated stack, or via nanowire arrays, in the terahertz regime [64], generally achieved using a semiconductor such as graphene as opposed to a metal in the layered structure [65], and also in the optical range [66], for sub-wavelength imaging [67,68], focusing [69], and other applications [70][71][72]. A common approach is to use highly conductive metals, such as gold or silver, for the metallic component, and dielectrics such as SiO 2 for the dielectric component.…”
Section: Hyperbolic Metamaterialsmentioning
confidence: 99%